Household Income in Cambodia: Gini Analysis - Vanny, Marvin; Sok, Vanny (Lembaga Yasin AlSys, 2024)
This study examined how income is distributed among rural households and the different sources that contribute to it, as well as their role in addressing income inequality. It used the Gini coefficient to assess the impact of rural household income and other sources of income on income equality in 16 villages in Chub commune, Tboung Khmum district, Tboung Khmum province, Cambodia. It was found that income from farm activities accounts for 68.78% of total income, and the income distribution is slightly unequal based on the Gini index and Lorenz curve (0.166614239; 0.169607843; 0.022865854). This suggests that diversification of income sources has influenced equality, highlighting the importance of households being able to diversify their income sources to achieve wealth equality. Access to resources such as inputs and finance could help improve income equality among rural families. The study highlights the need for policymakers to focus on the provision of productive resources and access to financial resources such as loans, as these can generate significant living income and potentially help prevent inequality in rural communities. Furthermore, the study revealed that non-farm and other activities contributed to the variation in income equality, accounting for 31.22% of the total income of rural households. The Gini index for non-farming income was 0.082741477; 0.176054916 compared to farming income, indicating slight inequality in household income.